Konstestasi Pilkada Dengan Calon Tunggal Prespektif Demokrasi Prosedural - Huda, Muhammad Khoirul (STAI Bumi Silampari, 2025)
The phenomenon of a single candidate in the election of regional heads (Pilkada) in Indonesia has become an interesting issue in the study of law and democracy. Since the Constitutional Court's decision No. 100/PUU-XIII/2015, the election mechanism with a single candidate has been carried out by presenting empty boxes as an alternative choice for voters. The existence of a single candidate in the Regional Elections has various implications for democratic principles, especially related to the right to vote guaranteed in the 1945 Constitution. This study aims to analyze the legal aspects of the existence of a single candidate in the Regional Elections, examine its conformity with the democratic principles embraced in the Indonesian constitutional system, and assess its impact on the legitimacy of the elected government. The results of the study show that the mechanism of a single candidate in the Regional Elections has been legally regulated in the applicable regulations, but it still poses a dilemma in the application of democratic principles. Although the empty box is intended as a solution to ensure the sustainability of the elections, this mechanism does not fully reflect healthy political competition, as it does not provide voters with real choice in determining their leaders. In addition, the dominance of major political parties and strict candidacy requirements are the main factors that hinder the emergence of alternative candidates. Therefore, more inclusive regulatory reforms are needed to increase political competition, strengthen public participation, and maintain substantive democratic principles in regional head elections in Indonesia.